رسالة الإمام مالك إلى الإمام الليث حول إتباع عمل أهل المدينة - دراسة تحليلية - - مسبل, اسماعيل (University of Eloued جامعة الوادي, 2022)
إن (عمل أهل المدينة) له أهمية بالغة عند علماء المذهب، وقد جاءت هذه الدراسة لتبين بعض جوانبه، من خلال مراسلة بين علمين جليلين، ووصلت إلى: أن الإمامين كانت بينهما محبة شديدة، ولم يمنعهما ردهما على بعضهما من الصلة، وأن العلماء كانوا أحرص على النصيحة، ومراعاة المقاصد عند الردود، وأن مراسلات الأئمة فيها علم كثير، وأن مالكا لم يكن يرى (العمل) من قبيل (الإجماع) ولا (العرف)، وإنما كان يراه نوعا من الاتفاق لا تجوز مخالفته؛ لوراثة أهل المدينة للسنن، وأنه لم يفرق بين الاتفاق النقلي والاجتهادي؛ لأنه لا بد من مستند من الوحي، وأنه بدأ عصر النقد الأصولي والحديثي زمن التابعين. The work of the people of Medina is of great importance to the scholars of the Maliki school of thought, and this study came to clarify some of its aspects, through a correspondence between two eminent scholars, and the study concluded: that two scholars had intense love between them, and their response to each other did not prevent them from the connection, and that the scholars They were more keen on advice, taking into account the purposes when responding, and that the correspondence of the imams contained a lot of knowledge, and that Malik did not see (work) as (consensus) nor (custom), but he saw it as a kind of agreement that cannot be violated; The people of Madinah inherited the Sunnahs, and he did not differentiate between the textual agreement and the jurisprudential agreement; Because it must be based on revelation, and that the era of fundamentalist and modern criticism began at the time of the followers.
Keywords: رسالة؛ مالك؛ الليث؛ عمل؛ المدينة. ; Message; Malik; Lith; Work; Medina.